2012
DOI: 10.1055/s-0032-1314787
|View full text |Cite
|
Sign up to set email alerts
|

β2 Adrenoceptor Signaling-induced Muscle Hypertrophy from Blood Flow Restriction: Is There Evidence?

Abstract: Skeletal muscle hypertrophy and increases in muscular function have been observed following low intensity/load exercise with blood flow restriction (BFR). The mechanisms behind these effects are largely unknown, but have been hypothesized to include a metabolic accumulation induced increase in muscle activation, elevations in growth hormone, and improvements in muscle protein balance. However, many of the aforementioned mechanisms are not present with BFR in the absence of exercise. In these situations, signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Furthermore, the increase in noradrenaline and insulin was higher in BFR-walk than in CON-walk. Insulin and noradrenaline appear to activate both phosphatidylinositol 3-kinase (Bolster et al, 2004;Loenneke et al, 2012b) and MAPK (Dash et al, 2003) signalling pathways. Recently, we found that a bout of BFR-walk had a positive effect on the activation of these pathways (Ozaki et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increase in noradrenaline and insulin was higher in BFR-walk than in CON-walk. Insulin and noradrenaline appear to activate both phosphatidylinositol 3-kinase (Bolster et al, 2004;Loenneke et al, 2012b) and MAPK (Dash et al, 2003) signalling pathways. Recently, we found that a bout of BFR-walk had a positive effect on the activation of these pathways (Ozaki et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated an increase in the norepinephrine concentration after BFR exercise (60,89), yet during EMS stimulated involuntary contraction with BFR, the increase was substantially less, possibly indicating that norepinephrine secretion depends on centrally mediated voluntary exertion (36). Loenneke et al (57) discussed the hypertrophic role of catecholamines through b2 adrenoceptor signaling-the most prominent adrenoceptor found in skeletal muscle tissue. The binding of catecholamines to b2 adrenoceptors initiates the G--protein--linked activation of the cyclic AMP secondary messenger, and then activation of protein kinase A dependent (e.g., inhibition of calcium--dependent proteolysis) and independent mechanisms (activation of the phosphatidylinositol--3--kinase pathway).…”
Section: Endocrine Responsesmentioning
confidence: 99%
“…β2 adrenergic receptor is widely distributed, this protein is expressed by airway smooth muscle (30-40000 per cell), epithelial and endothelial cells of the lung, smooth muscle of blood vessels, skeletal muscle, mast cells, lymphocytes, oral and skin keratinocytes and also by diverse cancer cells (Kohm and Sanders, 2001;Lutgendorf et al, 2003;Johnson, 2006;Sood et al, 2006;Thaker et al, 2006;Yang et al, 2006;Sastry et al, 2007;Yu et al, 2007;Liu et al, 2008a;Liu et al, 2008b;Shang et al, 2009;Sivamani et al, 2009;Yang et al, 2009;Bernabé et al, 2011;Bravo-Calderón et al, 2011-2012Steenhuis et al, 2011;Zhang et al, 2011;Loenneke et al, 2012).…”
Section: Expressionmentioning
confidence: 99%
“…Note Genetic and protein expression of β2 adrenergic receptor was demonstrated in OSCC by using RT-PCR assay, Western blot and immunohistochemistry (Shang et al, 2009;Bernabé et al, 2011;Bravo-Calderón et al, 2011-2012. Investigations performed in different oral cancer cell lines demonstrated that β2 adrenergic receptor signaling by norepinephrine increases cell proliferation and invasion, and upregulates interleukin-6 (IL-6) gene expression and protein release (Shang et al, 2009;Bernabé et al, 2011).…”
Section: Oral Squamous Cell Carcinoma (Oscc)mentioning
confidence: 99%